Quantifying Size and Number of Adipocytes in Adipose Tissue - Parlee, Sebastian D. (2014)
White adipose tissue (WAT) is a dynamic and modifiable tissue that develops late during gestation in humans and through early postnatal development in rodents. WAT is unique in that it can account for as little as 3% of total body weight in elite athletes or as much as 70% in the morbidly obese. With the development of obesity, WAT undergoes a process of tissue remodeling in which adipocytes increase in both number (hyperplasia) and size (hypertrophy). Metabolic derangements associated with obesity, including type 2 diabetes, occur when WAT growth through hyperplasia and hypertrophy cannot keep pace with the energy storage needs associated with chronic energy excess. Accordingly, hypertrophic adipocytes become overburdened with lipids, resulting in changes in the secreted hormonal milieu. Lipids that cannot be stored in the engorged adipocytes become ectopically deposited in organs such as the liver, muscle, and pancreas. WAT remodeling therefore coincides with obesity and secondary metabolic diseases. Obesity, however, is not unique in causing WAT remodeling: changes in adiposity also occur with aging, calorie restriction, cancers, and diseases such as HIV infection. In this chapter, we describe a semiautomated method of quantitatively analyzing the histomorphometry of WAT using common laboratory equipment. With this technique, the frequency distribution of adipocyte sizes across the tissue depot and the number of total adipocytes per depot can be estimated by counting as few as 100 adipocytes per animal. In doing so, the method described herein is a useful tool for accurately quantifying WAT development, growth, and remodeling.